Absence of Anastrepha grandis (Macquart, 1846) (Diptera: Tephritidae) in the coastal plain of Piauí, Brazil - Maria E. S. Valentim; Lanna L. G. S. O. Rocha; Gerane C. D. Bezerra-Silva; Márcio A. Silva (Entomological Communications)
Brazil is a large producer of cucurbits; despite the productive advantage, the country still has a low insertion in the international market due to the quarantine restrictions imposed by the Anastrepha grandis (Macquart, 1846) (Diptera: Tephritidae) presence. In this context, we conducted a study using McPhail traps and fruit sampling for three consecutive harvests to investigate the presence of A. grandis in commercial watermelon cultivation located in the Irrigation District of the Coastal Plateau of Piauí, Northeast Brazil. Anastrepha grandis was not registered in the coastal plain of Piauí, demonstrating the potential to establish a Pest Free Area. For this purpose, developing a pilot project on a larger time scale covering several properties and municipalities in Piauí is necessary.